From food price crisis to an equitable food system - Hawkes, Corinna; Ambikapathi, Ramya; Anastasiou, Kim; Brock, Jessica; Castronuovo, Luciana; Fallon, Naomi; Malapit, Hazel J.; Ndumi, Assumpta; Samuel, Folake; Umugwaneza, Maryse; Wanjohi, Milkah N.; Zorbas, Christina (Elsevier, 2022)
In 2022, the world is experiencing the greatest cost of living crisis in a generation.1 Crises have always highlighted inequities in our societies. With food prices at near record levels globally, rapidly rising inflation, and economic instability, many people living in situations of constraint have no choice but to skip meals, reduce the amount they eat, prepare meals with fewer nutritious foods, and buy cheaper, starchy staples and ultra-processed foods.2, 3 The implications for health inequalities are dire: increased dietary disparities will worsen food insecurity, undernutrition, obesity, and diet-related disease among those who are struggling most.